Utilization of agricultural wastes for the growth, leaf and soil chemical composition of cocoa seedlings in the nursery - E. I., Moyin Jesu; B., Atoyosoye (Universiti Putra Malaysia Press, 2002)
An experiment investigating the effectiveness of wood ash, cocoa pod husk, rice bran and oil palm bunch ash used ordinarily or in combination with duck and turkey manures on the leaf, soil chemical composition and growth of cocoa seedlings in the nursery, was conducted in Akure (Lat 7°N, 5°1()lE) in the rainforest zone of Nigeria during the period of 1997 to 1999. Twelve organic residue treatments, each applied at 30 g per 10 kg soil (6t/ha) in a polybag were compared to the NPK 15-15-15 (i.e recommended fertilization) applied 2 g per 10 kg soil (400 kg/ha) and a control treatment. The treatments were replicated four times and arranged in a completely randomized design. The residues and soils were chemically analyzed before seeds were sowed. Two cocoa seeds (Theobroma cacao (L.) were planted into each polybag and thinned to one plant after 14 days. The growth parameters such as plant height, leaf area, stem growth parameters such as plant height, leaf area, stem girth, leaf production, root and shoot dry weight were measured. The leaf nutrient contents and soil pH and organic C content were also determined. The results showed that the organic residue treatments significantly increased (p<0.05) the plant growth, leafN, P, K, Ca, Mg and Na contents soil pH and organic matter (O.M) compared to the control treatment. All the organic residue treatments increased the growth, leaf and soil nutrients more than NPK fertilizer treatment except for soils N and P. The low pH of the soils when fertilized with NPK delayed germination of cocoa seeds and the subsequent growth. Among plant residue treatments, the wood ash and oil palm bunch ash increased most the soil and leaf nutrient contents and growth parameters of cocoa seedlings while the soil treated with the combination of oil palm bunch ash + turkey manure indicated the best of growth, leaf and soil N, P, K, Ca, and Na contents, soil pH and organic matter content.